Non-invasive Assessment of Pulmonary Artery Wave Reflection in Dogs With Suspected Pulmonary Hypertension - Yoshida, Tomohiko; Matsuura, Katsuhiro; Seijirow, Goya; Uemura, Akiko; Yilmaz, Zeki; Tanaka, Ryou (Frontiers in Veterinary Science, 2021)
Background: Pulmonary arterial wave reflection (PAWR) occurs when the forward blood flow out the right ventricle is reflected by the pulmonary arterial tree, generating a backward wave. PAWR assessed by cardiac catheterization has been used to obtain information regarding pulmonary artery hemodynamics in pulmonary hypertension (PH) in people. However, diagnostic cardiac catheterization is not commonly used in small animal medicine because it is invasive and requires anesthesia. Hypothesis/Objective: To investigate whether PAWR can be assessed non-invasively in dogs with suspected PH using Doppler echocardiography, based on wave intensity analysis (WIA). In addition, the method was validated in a dog model of acute pulmonary embolism. Animals: Fifty-one client-owned dogs with tricuspid valve regurgitation were included in the clinical study (thirty-five with suspected PH and sixteen without echocardiographic evidence of PH) and eight healthy beagle dogs were included in the validation study. Methods: PAWR was assessed by separating pulmonary artery pulse pressure waveforms, which were estimated from the flow profile of tricuspid regurgitation, into forward (Pf) and backward pressures (Pb) using WIA. Reflection coefficient (RC) was defined as the ratio of peak Pb to peak Pf. We investigated the relationships between RC, cause, and survival time in dogs with suspected PH. In addition, we performed a validation study to compare PAWR obtained by cardiac catheterization and PAWR by Doppler echocardiography in dogs with experimentally-induced PH. Results: RC was significantly higher in dogs with suspected PH than in dogs without echocardiographic evidence of PH (0.18 ± 0.13 vs. 0.59 ± 0.21, P < .001). A characteristic reflected waveform appeared depending on the cause of PH. Kaplan-Meier survival curves showed that dogs with RC > 0.48 had a significantly shorter survival time than dogs with RC < 0.48 (x2 = 9.8, log-rank test, p = 0.0018, median survival time 353 days vs. 110 days). In the validation study, RC obtained by Doppler echocardiography was significantly correlated with RC obtained by cardiac catheterization (r = 0.81, P < .001). Conclusions: PAWR analysis performed by echocardiography seems feasible in dogs and could provide useful information for classification and prognosis in canine PH.